An investigation on the use of oedometer method for determination of liquid limit value of soil - Vickram , Alakuventhan (2014)
Consistency limits are extensively used in geotechnical engineering practice. These limits are commonly referred to the Atterberg Limits and the limits are the liquid limit, plastic limit and shrinkage limit. Consistency limits is potentially useful as an index property for predicting the behaviour of clay soils. The liquid limit in particular is used in many correlations with engineering properties. It provides a good basis form predicting the soil properties such as deformability, expansion, hydraulic conductivity and strength. Therefore, liquid limit has strong links to underlying mechanical behaviour. However, the determination of the liquid limit by Casagrande Liquid Limit Device and Cone Penetration Method which are in international standards have their own limitation as they requires several points to determine liquid limit of soil as these both methods uses trial and error method. This study presents the investigation on the use of oedometer method as an alternative way to determine the liquid limit of zeolite from saturated slurried condition by using a small consolidation pressure of 0.9 kPa and 6 kPa. Thus by doing this, one can determine the liquid limit by one point determination technique as the equilibrium water content reached from the consolidation will be equivalent or nearer to the liquid limit of soil under the consolidation pressure either 0.9 kPa or 6 kPa. The physical properties of zeolite were determined and the liquid limit of zeolite was determined from cone penetration method. The test results shows that by using a consolidation pressure of 0.9 kPa, the value of liquid limit obtained from oedometer method is much nearer to the value of liquid limit obtained from the cone penetration method and the difference between those values obtained is less than 1%. Meanwhile, the liquid limit value obtained by using consolidation pressure of 6 kPa does not tally and far away from the value of liquid limit obtained from cone penetration method. Hence, by using consolidation pressure of 0.9 kPa, oedometer method can be used to determine the liquid limit of soil and for consolidation pressure of 6 kPa, other methods or different soil should be used and applied for determination of liquid limit value.